THE ANALYSIS AND DESIGN OF GUIDED INQUIRY E-WORKSHEET BASED TO DEVELOP HIGH ORDER THINKING SKILLS - Riyadi, Beli; Ertikanto, Chandra; Suyatna, Agus (International Journal of Research -GRANTHAALAYAH, 2018)
The aims of this research were to analyze the needs and to design electronic worksheet to develop High Order Thinking Skills (HOTS) in static fluid material at Islamic High School Ar Raihan and SMAN 6 Bandar Lampung. The research method used in this study was two steps of Research and Development (R&D) with mixed methods. Step 1: analyze the needs by doing: (a) front end analysis including analyze the needs of teachers and students, and (b) learner analysis which focused on students’ HOTS with pre experimental design i.e. one shot case study. Step 2: make hypothetic design of e-Worksheet through Focus Group Discussion (FGD). The study results show the information from front analysis that the analysis of teachers need is 75% hasn’t mastered the newest multimedia yet, find difficulties in leading the students to think scientifically, and have not developed appropriate e-worksheet. The analysis of students need shows that 72% students were interested in electronic learning media, 88% hasn’t be familiar with experiment method and there is no appropriate e-worksheet as they wished yet. Learner analysis shows that Sign 2 tailed 0,000 < 0,05 so that the students mostly don’t have HOTS yet. Finally, tested design is obtained from Guided Inquiry based e-worksheet to develop HOTS.